1986
DOI: 10.1016/0014-5793(86)80632-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐mediated targeting of liposomes to red cells in vivo

Abstract: Drug targeting Liposome Cell‐specific antibody F(ab')2 fragment (Erythrocyte)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…5 C and D). Previous work has shown that the plasma half-lives of liposomes and ovalbumin can be extended via fusion to anti-RBC antibodies (39) or peptides (40). Our molecule exhibited a similarly extended terminal plasma half-life, which was nearly twice as long in huGYPA transgenic mice compared with nontransgenic mice (28.3 h vs. 15.5 h) (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…5 C and D). Previous work has shown that the plasma half-lives of liposomes and ovalbumin can be extended via fusion to anti-RBC antibodies (39) or peptides (40). Our molecule exhibited a similarly extended terminal plasma half-life, which was nearly twice as long in huGYPA transgenic mice compared with nontransgenic mice (28.3 h vs. 15.5 h) (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Given this scarcity of adequate antigens exposed on pRBCs, essential parameters that will be determinant in the capacity of iLPs to recognize and bind target cells are a careful selection of sufficiently specific antibodies, the way they are crosslinked to lipids, and their numbers on the liposome surface. Since RBCs have very poor endocytic processes [17], once iLPs are docked to them delivery of cargo into the cell has been proposed to occur through a membrane fusion process [7,10,18,19]. Nevertheless, considering the lack of strong evidence and the poor characterization of this fusion process using RBCs and pRBCs as targeted cells, alternative mechanisms of interaction should be considered.…”
Section: Introductionmentioning
confidence: 96%
“…Liposomal nanovectors bearing cell-specific antibodies on their surfaces (immunoliposomes, iLPs) have been widely considered as chemotherapeutic drug carriers due to their non-toxic and biodegradable character [6], but they have not progressed yet towards a working strategy for malaria therapeutics. Pioneering assays to treat Plasmodium berghei infections in mice focused on the encapsulation of the antimalarial drug chloroquine into liposomes (LPs) and iLPs functionalized with antibodies against RBCs and pRBCs [7][8][9]. Drug efficacy was significantly improved upon encapsulation, especially when targeted towards pRBCs, and after treatment with iLPs, mice exhibited lower parasitemias and longer survival times even with drug-resistant strains.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the covalent attachment of antibodies to Ls specifically enhanced their binding to rat erythrocytes in vivo and reduced their uptake by the liver and therefore can be used to target antimalarials to erythrocytes [146,310,311]. MAb F10-bearing Ls containing CQ were produced and its efficacy was evaluated in mice infected with CQ-susceptible or CQ-resistant P. berghei [145].…”
Section: Malariamentioning
confidence: 99%